(untitled) (Journal of Human Sciences, 2021)
The aim of the present research is to study and preserve the human mind as a significant purpose of the Islamic law (shariah). The researcher functionalized a concept of religious discourse as the privacy of talking to others. Human mind is a most magnificent bounty bestowed by- God to whom be ascribed all perfection and majesty- upon human beings. Much interest inreligious discourse was given a primary concern with the psycho-educational dimention, to control human behavior as well as guiding it to address the whole nation to the Holly Quran and the Sunnah of Mohammad(blessings and peace be upon him) that preserve human mind, protecting it from the blights that hinder its functions towards his Creator and the human society. This research has concluded a number of findings. The most important one is moral educational guidance and Islamic education, as it required in both the Holly Quran and Sunnah of prophet Mohammad (peace be upon him) , which is the most significant method that preserve human mind The research has also revealed that human beings can protectthem selves through participating in buildingsociety by mind preservation.